Mycobacterium ulcerans infection: evolution in clinical management. Issue 7 (19th September 2012) - Simpson, Candice; O'Brien, Daniel P.; McDonald, Anthony; Callan, Peter
Abstract Mycobacterium ulcerans causes significant morbidity in various endemic locations in Australia and West Africa. The commonest presentation is as a necrotic ulcer often with surrounding subcutaneous necrosis and oedema, which can cause significant morbidity, deformity and functional impairment. Traditional treatment was wide excision and debridement with grafting or flap reconstructions further adding to morbidity and with high recurrence rates. Following publication of clinical studies where antibiotics were shown to be effective, treatment has moved towards combination management with systemic antibiotics and limited surgery involving mainly debridement of the ulcers. Identification of the 'paradoxical' immune‐reconstitution syndrome has also impacted upon the extent of excision required. This paper will present the evolution in clinical management of M. ulcerans cases on the Bellarine Peninsula, Victoria, Australia.